(untitled) (Journal of Dhaka National Medical College & Hospital, 2016)
Background: Children of under 15 comprises one third of our population and more than half of total deaths occurs in this group which is the major health problem of our country. An understanding of epidemiological trend in hospital admissions including disease pattern, is critical for health care planning, including effective case management strategies, appropriate resource allocation and improving existing services facilities. Objectives: To evaluate the disease pattern among children for reducing the morbidity and mortality rate and also to identify the demographic profile of the patients attending in the department of paediatric, Dhaka National Medical College Hospital (DNMCH). Materials and Methods: This was a prospective study. Sample collected of all patients admitted in the department of pediatrics, DNMCH, from 1st Jan 2015 to 30th June 2015 were analyzed. Result: Total 432 patients (aged 1 day to 12 years) were admitted during this study period; among them Neonate 19.21%, Infant (1month-12 month) 24.30%, preschool age group (1-5 years) 33.56% and children (6 years-12 years age) 22.9%. Among the admitted cases, Acute Respiratory Infection (ARI) 53%, Diarrhoea (33.33%), Bronchial Asthma (4.76%), Enteric fever (2.86%) in infant (1-12 month age group). Enteric fever and Diarrhoea, were found as top two causes of admission in Preschool age (1-5 yrs age group) and Children (6-12 yrs age group). Most frequent five diseases in case of neonates (1-28 days age group) from admission are shown in this study. Among the admitted neonates, Perinatal Asphyxia (30.12% ), Neonatal Jaundice (24.09% ), Neonatal Sepsis ( 20.48%), preterm Low Birth Wt. (18.07%), Intra uterine growth retardation (IUGR) 3.6%. Maximum of our patients are found male (51.62%) and 48.38% are female. The maximum patients about 74.54% have come form old part of Dhaka city. Among the admitted patients live in concrete house about 48.61% and 41.67% housing are semi-concrete. The patients family member are (4-5 person) about 52.55%, 45.83% family member are (2-3 person). Conclusion: Finding of this study helps us to understand Paediatric admission trend and disease pattern of this institution, which are essential for health sector planning, including effective case-management strategies J. Dhaka National Med. Coll. Hos. 2016; 22 (01): 18-23